Acute lymphoblastic leukemia in a child with hemoglobins S and Q-Iran - Gürgey, Aytemiz; Özsoylu, Şinasi; Hiçsönmez, Gönül; Irken, Gülersu; Altay, Çidem (The Turkish Journal of Pediatrics, 1990)
A 13-year-old girl with acute lymphoblastic leukemia is presented. The peripheral smear showed, in addition to lymphoblasts, marked anisocytosis, poikilocytosis, and polychromasia. In vitro sickling test was positive. Hemoglobin electrophoresis at pH 9.0 on starch gel revealed the presence of hemoglobin A, hemoglobin S, and a band with a mobility of hemoglobin A₂. Structural analysis revealed the presence of hemoglobin S and an alpha-chain variant, hemoglobin Q-Iran. The patient attained remission with the initial therapy administered but a relapse occurred five months later. Our study indicates the need for detailed investigation of leukemia patients in which abnormal hemoglobins are prevalent.
Keywords: acute lymphoblastic leukemia; hemoglobin S; hemoglobin Q-Iran